2011
DOI: 10.1038/hr.2011.64
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces microtubule reorganization mediated by a deacetylase SIRT2 in endothelial cells

Abstract: Angiotensin II has been implicated in vascular remodeling. Microtubule composed of tubulins regulates cell shape, migration and survival. Tubulin acetylation has an important role in the control of microtubule structure and microtubule-based cellular functions. In this study, angiotensin II induced disassembly and deacetylation of a-tubulin, which were blocked by pretreatment with an angiotensin II type 1 receptor blocker losartan and a sirtuin class deacetylase inhibitor sirtinol, and by depletion of a deacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…A previous study has shown that Sirt2 may be implicated in mediating angiotensin II-induced endothelial cell migration via modulating α-tubulin acetylation and microtubule reorganization [40]. Consistent with this observation, we identified (and confirmed with qPCR) that Sirt2 knock down altered the expression of several genes involved in cytoskeletal organization, cell contraction and migration, such as CALD1 (caldesmon) and CNN2 (calponin) [41,42].…”
Section: Resultssupporting
confidence: 88%
“…A previous study has shown that Sirt2 may be implicated in mediating angiotensin II-induced endothelial cell migration via modulating α-tubulin acetylation and microtubule reorganization [40]. Consistent with this observation, we identified (and confirmed with qPCR) that Sirt2 knock down altered the expression of several genes involved in cytoskeletal organization, cell contraction and migration, such as CALD1 (caldesmon) and CNN2 (calponin) [41,42].…”
Section: Resultssupporting
confidence: 88%
“…The relative abundance of microtubule and NOX2 protein subunits in the adult mdx compared with the adult wild type is indirectly supported by the increase in mRNA transcript in both mdx mice and human DMD patients. The presence of the transforming growth factor–β (50) and angiotensin (51) signaling pathways in our network is also notable because of reports that both signaling cascades act to increase microtubule protein content and network density (52, 53) and are activated in human DMD muscle. Furthermore, we and others have shown that inhibition of these pathways is beneficial in both human DMD patients (54) and mdx mice (55).…”
Section: Discussionmentioning
confidence: 84%
“…In endothelial cells (ECs), SIRT1 uniquely regulates cell physiology by controlling endothelial homeostasis and vascular functionality by modulating endothelial nitric oxide synthase (eNOS) activity, p53, angiotensin II (Ang II) type 1 receptor (AT1R), and forkhead box O (FOXO) 1. An emerging role of SIRT2 has been described in the hypertension-induced vascular remodeling (65), whereas SIRT3 controls systemic levels of oxidative stress and increases EC survival in response to hypoxia acting on FOXO3/manganese superoxide dismutase (MnSOD) signaling pathway (96,146,195). SIRT4 and SIRT7 aggravate cardiac hypertrophy and negatively affect the proliferation and migration of ECs and vascular smooth muscle cells (VSMCs) (20,199).…”
mentioning
confidence: 99%